Refining treatment strategies for iron deficient athletes - McCormick, R.; Sim, M.; Dawson, B.; Peeling, P. (Sports Medicine, 2020)
Iron deficiency (ID) is a prevailing nutritional concern amongst the athletic population due to the increased iron demands of this group. Athletes` ability to replenish taxed iron stores is challenging due to the low bioavailability of dietary sources, and the interaction between exercise and hepcidin, the primary iron-regulatory hormone. To date, copious research has explored the link between exercise and iron regulation, with a more recent focus on optimising iron treatment applications. Currently, oral iron supplementation is typically the first avenue of iron replacement therapy beyond nutritional intervention, for treatment of ID athletes. However, many athletes encounter associated gastrointestinal side-effects which can deter them from fulfilling a full-term oral iron treatment plan, generally resulting in sub-optimal treatment efficacy. Consequently, various strategies (e.g. dosage, composition, timing) of oral iron supplementation have been investigated with the goal of increasing fractional iron absorption, reducing gastric irritation, and ultimately improving the efficacy of oral iron therapy. This review explores the various treatment strategies pertinent to athletes and concludes a contemporary strategy of oral iron therapy entailing morning supplementation, ideally within the 30 min following morning exercise, and in athletes experiencing gut sensitivity, consumed on alternate days or at lower doses.